(untitled) (Ameghiniana, 2014)
Petrified woods of Schinopsixylon heckii Lutz and Menendoxylon piptadiensis Lutz are described from Upper Pleistocene sediments of Concordia, Entre Ríos Province, Argentina. The fossil descriptions are based on anatomically preserved stems. These fossils were found in the El Palmar Formation.